2001
DOI: 10.1163/156856201744470
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical quantitative structure activity relationships to avoid mutagenicity in dental monomers

Abstract: The objective of this study was to identify through quantum mechanical quantitative structure activity relationships (Q-QSARs) chemical structures in dental monomers that influence their mutagenicity. AMPAC, a semiempirical computer program that provides quantum mechanical information for chemical structures, was applied to three series of reference chemicals: a set of methacrylates, a set of aromatic and a set of aliphatic epoxy compounds. QSAR models were developed using this chemical information together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Many SARs with quantum chemical descriptors have been reported for aquatic species 13) , and the SAR of estrogen-like bisphenol A analogs for breast cancer MCF-7 was reported previously using quantum chemical descriptors 14) . Furthermore, using AMPAC, a semiempirical computer program, SARs have been used to accurately predict the mutagenicity of bis-GMA, a monomer commonly used in dentistry 15) . Similarly, conformational and quantum analyses of dental adhesive carboxylic acid and carboxylic acid anhydride monomers have been performed using a semiempirical computer program 16) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many SARs with quantum chemical descriptors have been reported for aquatic species 13) , and the SAR of estrogen-like bisphenol A analogs for breast cancer MCF-7 was reported previously using quantum chemical descriptors 14) . Furthermore, using AMPAC, a semiempirical computer program, SARs have been used to accurately predict the mutagenicity of bis-GMA, a monomer commonly used in dentistry 15) . Similarly, conformational and quantum analyses of dental adhesive carboxylic acid and carboxylic acid anhydride monomers have been performed using a semiempirical computer program 16) .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was found that chemical hardness played a key role in the cytotoxic activity of methoxyphenolic compounds against human oral tumor cells 19) . However, with regard to the use of computational chemistry for SAR studies of methacrylates 15,17,18) , the reports are comparatively scarce. The aim of the present study, therefore, was to re-investigate the mechanism of methacrylateinduced toxicity based on SAR.…”
Section: Introductionmentioning
confidence: 99%
“…As we have illustrated in other publications [2,3], such a computationally derived model can also provide direction for the modification of existing monomers to improve performance. Since the frequency of the dental curing light is fixed, our approach to develop-ing a QSAR for these materials is based on molecular structure leading to differences in polarizability, and hence refractive index.…”
Section: Introductionmentioning
confidence: 89%
“…In this study, we have selected a data set of 15 cycloaliphatic epoxides for the mutagenicity data reported by Yourtee et al [15]. The mutagenic parameters studied here are the slopes of revertants vs. nanomoles of the test chemical in the Salmonella test strain TA100 with the natural logarithm of the slopes (ln(TA100)) used in the QSARs models.…”
Section: Data Set and Computational Strategiesmentioning
confidence: 99%
“…As can be seen, these models are statistically significant because of their p , 0:05: This confirms that all variables conforming to the models are significant and essentially all of them could be used for predicting the studied property of this set of compounds. Furthermore, all models have the same number of significant variables and in all of them the same training set was used, which was formed by 15 compounds, as it is shown in Table 1 [15]. However, there are remarkable differences related with the explanation of the experimental variance ðR 2 Þ and their standard deviation ðSÞ are also different.…”
Section: Quantitative Structure Association Constant Relationsmentioning
confidence: 99%